1995
DOI: 10.1086/309827
|View full text |Cite
|
Sign up to set email alerts
|

Locally Optimally Emitting Clouds and the Origin of Quasar Emission Lines

Abstract: The similarity of quasar line spectra has been taken as an indication that the emission line clouds have preferred parameters, suggesting that the environment is subject to a fine tuning process. We show here that the observed spectrum is a natural consequence of powerful selection effects. We computed a large grid of photoionization models covering the widest possible range of cloud gas density and distance from the central continuum source. For each line only a narrow range of density and distance from the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
403
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(426 citation statements)
references
References 27 publications
(29 reference statements)
23
403
0
Order By: Relevance
“…Regardless of the variation across selection criteria, luminosities and redshifts, a remarkable similarity in the overall shape is visible over a wide wavelength range. The simultaneous existence of lines arising in such different environments around objects differing by many orders of magnitude in luminosity is caused by the varying conditions in the emitting clouds which ensure that each ionic species has optimal conditions to produce line emission (Baldwin et al 1995). Significant differences between the composites are visible blueward of Lyα where different methods for IGM absorption correction has been employed.…”
Section: Comparison To Existing Compositesmentioning
confidence: 99%
“…Regardless of the variation across selection criteria, luminosities and redshifts, a remarkable similarity in the overall shape is visible over a wide wavelength range. The simultaneous existence of lines arising in such different environments around objects differing by many orders of magnitude in luminosity is caused by the varying conditions in the emitting clouds which ensure that each ionic species has optimal conditions to produce line emission (Baldwin et al 1995). Significant differences between the composites are visible blueward of Lyα where different methods for IGM absorption correction has been employed.…”
Section: Comparison To Existing Compositesmentioning
confidence: 99%
“…Estimated Lyα flux does not include the strong wings beyond ±0.5 eV from the core of the line. pare the estimated line flux ratios to the fluxes from the compilation of Baldwin et al (1995). All the fluxes are expressed in the units of Lyα flux.…”
Section: Appearance Of the Blrmentioning
confidence: 99%
“…Korista, Ferland & Baldwin (1997a) suggested that the BLR does not see the same SED we do. They adopt a baseline of 0.1 for the BLR CF, and use the Locally Optimally emitting Cloud (LOC) model of the BLR, where a single slab of gas produces line emission from a rather limited range of ionization states (Baldwin et al 1995). However, adopting the observed BLR CF of ≃0.3 (see above), and noting that a single slab produces line emission from a very broad range of ionization states (Baskin et al 2014a), alleviate the need in a different SED for the BLR.…”
Section: Similar Relations For the Broad Line Region C Iv Emissionmentioning
confidence: 99%